FRI0561 PRO-INFLAMMATORY DIETS ARE ASSOCIATED WITH INCREASED C-REACTIVE PROTEIN AND RHEUMATOID ARTHRITIS IN THE UK BIOBANK COHORT. (13th June 2020) - Dainty, J.; Sayers, E.; Yates, M.; Macgregor, A.
Abstract : Background: Several individual dietary components have been associated with the risk of rheumatoid arthritis (RA) and recent studies have suggested that dietary indices, which account for the consumption of multiple foods, can be used as more complete measures of risk. Objectives: In this study we aimed to use the Dietary Inflammatory Index (DII), an independent index of dietary variable associated with inflammatory biomarkers, to evaluate potential associations between pro-inflammatory exposures in the diet, an inflammation biomarker (C-reactive protein) and RA onset using the UK Biobank cohort. Methods: The DII was calculated from data obtained in 24-hour dietary recall questionnaires collected on healthy participants on four separate occasions over an approximate annual period between Feb 2011 and April 2012. Cases of RA in the UK Biobank cohort were identified from the participants with appropriate ICD10 codes and compared against a randomly selected subsample of controls matched (20:1) for age, sex, smoking status and BMI. Results: Among the 502, 519 subjects enrolled in Biobank, 141, 769 had completed 24-hour dietary recall questionnaires and had full data for the 18 dietary variables that were required to create the DII (mean=0.03, range: -3.88, 4.22). Higher (positive) DII values indicate more pro-inflammatory diets. This index was positively correlated (p<0.001) with C-reactive protein (CRP), attesting to the validity of this index for assessing dietary inflammatory potential. A total of 1, 423 participants were classified as having RA (1% prevalence in 'dietary' cohort of 141, 769) according to their ICD10 codes that were last updated in 2018. Their mean age at enrolment (2006-10) was 59 years. There was a significant association between DII and RA: OR 1.05 [1.01-1.09]; p=0.028) that suggested RA cases were more likely to be consuming a pro-inflammatory diet. Conclusion: These data show a significant association between diet, inflammation (CRP) and RA in the UK Biobank population. The findings are consistent with a recent analysis of the US Nurse's Health Study which was based on data only from females, indicating that these findings are likely to be robust and generalisable. Diet is one of the few modifiable factors that has the potential to reduce the risk of future RA onset. These results open the way to providing evidence-based health advice and for designing clinical interventions. References: [1] Shivappa N, Steck SE, Hurley TG, Hussey JR, Hebert JR. Designing and developing a literature-derived, population-based dietary inflammatory index. Public health nutrition 2014;17:1689-96. Acknowledgments: This research has been conducted using the UK Biobank Resource under Application Number '33557' Disclosure of Interests: None declared